An outline of John Calvin’s teachings on the Church in the light of Institutio Religionis Christianae (1543) - Wodziński, Grzegorz (Saeculum Christianum. Pismo Historyczne, 2021)
One of the main postulates of the reformation movement, apart from the theological questions, was a proposal of the internal reform of the church institution. The Father of the Reformation, as Rev. Martin Luther is called in the source literature, raised the questions concerning the mission of the Church, its role in the magisterium, and, perhaps above all, its hierarchical structure and the role of the clergy in the process of eternal salvation. As a result of his reflections, observations, and personal experience, Luther successively undermined different dogmatic, theological questions, as well as those regarding the organization of the Roman Catholic Church. Slogans of renewal and reforms of the church structure spread very rapidly through the territory of German Reich, gaining numerous supporters among the European states. One of those for whom the Reformation ideas became the main field of activity was John Calvin of France. A well-rounded, well educated, and well-read lawyer, familiar with the main works of the German monk, Calvin’s principal theses postulated changes in the functioning of the Church. Additionally, Calvin proposed to distinguish between two dimensions of the Church, i.e. the earthly (visible) and the heavenly (invisible) one, with Jesus Christ as the highest priest, bonding the Church together and guaranteeing its unity, permanence, and indivisibility. Calvin’s opus magnum, Institucio Religionis Christianae, represents to the fullest his vision of the Christian Church as he thought it should be. An analysis of specific issues regarding the function of the clergymen, the role of the pope, the celebration of the sacraments, penance and conversion, as well as eternal salvation, gives an insight into the basic compendium of ecclesiological knowledge compiled by Calvin. His teachings about the Church, although in some points different from those of Rev. Martin Luther, nonetheless oscillate within the principal slogans of Reformation: Sola Fides – the man is saved solely by faith, Sola Gratia – God’s grace is necessary for salvation, Sola Scriptura – the only source of faith is the Holy Bible. Calvin’s own idea was that of Solus Christus – salvation can be reached solely through Christ as the centre of the Church. Calvin’s Christ-centric attitude reveals itself to the fullest in his preaching and the ideological foundations he established for the reformed denomination.